2013
DOI: 10.1155/2013/391984
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Role of Indoleamine 2,3-Dioxygenase and Tryptophan Metabolites in Infectious Diseases: Potential Role in Macrophage-Mediated Inflammatory Diseases

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1), the L-tryptophan-degrading enzyme, plays a key role in the immunomodulatory effects on several types of immune cells. Originally known for its regulatory function during pregnancy and chronic inflammation in tumorigenesis, the activity of IDO1 seems to modify the inflammatory state of infectious diseases. The pathophysiologic activity of L-tryptophan metabolites, kynurenines, is well recognized. Therefore, an understanding of the regulation of IDO1 and the subsequent bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 87 publications
(84 reference statements)
3
56
0
3
Order By: Relevance
“…IFN-␥ represents the principal IDO inducer, and other inflammatory stimuli also induce IDO, including TNF-␣, IL-6, IL-1␤, and lipopolysaccharide (LPS), although markedly less than IFN-␥ (26)(27)(28)(29). In the present study, TNF-␣ synergized with IL-6 to mediate IDO induction in EBV-MDMs and did not necessarily require the synthesis of IFN-␥.…”
Section: Discussionmentioning
confidence: 47%
“…IFN-␥ represents the principal IDO inducer, and other inflammatory stimuli also induce IDO, including TNF-␣, IL-6, IL-1␤, and lipopolysaccharide (LPS), although markedly less than IFN-␥ (26)(27)(28)(29). In the present study, TNF-␣ synergized with IL-6 to mediate IDO induction in EBV-MDMs and did not necessarily require the synthesis of IFN-␥.…”
Section: Discussionmentioning
confidence: 47%
“…IDO is well-known for its checkpoint role in the immune system. Abnormal excessive IDO is frequently observed in a variety of diseases (8). Intriguingly, it has been demonstrated that IDO can modulate vascular tone and play an important role in cerebral ischemia-reperfusion in a mouse model (9).…”
Section: A Series Of Nbp Potential Targets Resulting From Search Are mentioning
confidence: 99%
“…A modest, yet significant correlation was observed between TGF-βR1 and IFN-γR1. While many in vitro experimental studies have well demonstrated how IDO is induced by TGF-β and IFN-γ [17,18], correlations between these particles in tumor specimens are not widely described. Lee et al found significant correlations between genes encoding both TGF-β and IFN-γ with the Indo gene encoding IDO (R = 0.95 and R = 0.78, respectively; p < 0.0001) [19].…”
Section: Discussionmentioning
confidence: 99%